Proof‐of‐concept: neonatal intravenous injection of adeno‐associated virus vectors results in successful transduction of myenteric and submucosal neurons in the mouse small and large intestine. Issue 2 (12th November 2015) - Buckinx, R.; Van Remoortel, S.; Gijsbers, R.; Waddington, S. N.; Timmermans, J.‐P.
Abstract: Background: Despite the success of viral vector technology in the transduction of the central nervous system in both preclinical research and gene therapy, its potential in neurogastroenterological research remains largely unexploited. This study asked whether and to what extent myenteric and submucosal neurons in the ileum and distal colon of the mouse were transduced after neonatal systemic delivery of recombinant adeno‐associated viral vectors (AAVs). Methods: Mice were intravenously injected at postnatal day one with AAV pseudotypes AAV8 or AAV9 carrying a cassette encoding enhanced green fluorescent protein (eGFP) as a reporter under the control of a cytomegalovirus promoter. At postnatal day 35, transduction of the myenteric and submucosal plexuses of the ileum and distal colon was evaluated in whole‐mount preparations, using immunohistochemistry to neurochemically identify transduced enteric neurons. Key Results: The pseudotypes AAV8 and AAV9 showed equal potential in transducing the enteric nervous system (ENS), with 25–30% of the neurons expressing eGFP. However, the percentage of eGFP‐expressing colonic submucosal neurons was significantly lower. Neurochemical analysis showed that all enteric neuron subtypes, but not glia, expressed the reporter protein. Intrinsic sensory neurons were most efficiently transduced as nearly 80% of calcitonin gene‐related peptide‐positive neurons expressed the transgene. Conclusions & Inferences: The pseudotypes AAV8 and AAV9 can be employed for gene delivery to both the myenteric and the submucosal plexus, although the transduction efficiency in the latter is region‐dependent. These findings open perspectives for novel preclinical applications aimed at manipulating and imaging the ENS in the short term, and in gene therapy in the longer term. Abstract : Adeno‐associated viral vectors, AAV8 and AAV9, can be employed for gene delivery to both the myenteric and the submucosal plexus, although the transduction efficiency in the latter is region‐dependent. These findings open perspectives for novel preclinical applications aimed at manipulating and imaging the ENS in the short term, and in gene therapy in the longer term. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility/id1074924884 Youtube:https://www.youtube.com/watch?v=llv7kzQzn9w&feature=youtu.be